Pelatihan Alat Pemotong Bambu Otomatis Berbasis Mikrokontroler Menuju Kampung Produktif di Desa Ngajum Gunung Kawi Malang (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2017)
Ngajum Gunung Kawi Village Malang Regency East Java there are many home industries of bamboo cutting production. The expansion marketing is resulted the workers in over time to process of cutting bamboo. The process of cutting bamboo is done manually, so it takes a long production time, high risk of work accidents, and more labors. The training conducted in collaboration with Partners to solve problems that faced by Partners, among others, training the use of automatic bamboo cutting tools, training and assistance of automatic equipment maintenance in bamboo cutting, as well as training and management assistance in bamboo cutting production. Tools made include bamboo cutting tools as a substitute for the process of manual cutting and bamboo smoothing tool after bamboo cut in the final stage. The design of the two tools can provide renewal of science in terms of science and technology, the implementation of microcontroller as a tool controller, minimize work accidents during bamboo cutting production, and optimize the production results in terms of production time. Production results increased after using the automatic bamboo cutting and bamboo smoothing tool, which is 25 kg / day to 100kg / day.